Plant centromere biology - Jiang, Jiming; Birchler, James A. (James Arthur), 1950- (Ames, Iowa : Wiley-Blackwell, 2013)
Plant Centromere Biology is dedicated to plant centromere research. Chapters cover the structure of centromeres from several plant species including Arabidopsis thaliana, rice, maize, wheat and beet, while other sections cover several unique characteristics associated with plant centromeres, including classical and modern neocentromeres, centromere drive and centromere misdivision. Additional chapters are dedicated to epigenetic modification and evolution of plant centromeres, and development and application of plant artificial chromosomes. Written by an international group o.
Distribution of CENH3 in pollen nuclei and its resetting in the zygoteEpigenetic regulation of kinetochore assembly; Functional requirement of N- and C-terminal parts of CENH3; Recognition of A. thaliana centromeres by heterologous CENH3; Deregulation of CENH3 activity in plants; Interaction of CENH3 with centromeric DNA; Regulation of CENH3 expression by the E2F transcription factor family; CENH3 levels at centromeres decline with the age of tissue; CENH3, from basic research to agricultural application; Acknowledgments; References; 7: Holokinetic Centromeres.
Edition statement from running title area.
Includes bibliographical references and index.
Print version record.
Keywords: Plant molecular genetics; Plant genomes; Plant physiology; Centromere; Botany; Botany; Centromere; Plant genomes; Plant molecular genetics; Plant physiology; SCIENCE -- Life Sciences -- Molecular Biology; Electronic books; Electronic books